display | more...

There are times in the life of a mathematician when he must solve a quadratic equation without the use of the quadratic formula. Typically, this occurs in math classes, but it also proves useful when dealing with polynomials of higher degree. Example 1:

(x-3)(x+1) = 0.

So we know that multiplying those two terms together produces zero. This can only happen if at least one of the terms is itself equal to zero. Therefore, either
x - 3 = 0 or
x + 1 = 0.
Anyway, you will not need to be a genius to observe that x is therefore 3 or -1. In this case, of course, it is not possible for both terms to be 0; x cannot equal 3 and -1 at the same time.

That was a rather simple example however. Example 2: What if we were to solve 6x²- 3x - 3 = 0 by factorizing. The methods for factorizing are discussed elsewhere, but for now you can take it on trust that

6x²- 3x - 3 = (2x+1)(3x-3)

If (2x+1)(3x-3) = 0, we can deduce that either
2x + 1 = 0 or
3x - 3 = 0.
Again, very basic manipulation of these equations will indicate that x = -½ or x = 1. As before, these solutions are mutually exclusive.

Example 3: For a final equation, we shall observe the equation 4x² + 4x + 1 = 0. It is no coincidence that 4x² + 4x + 1 = (2x + 1)(2x + 1) = (2x + 1)². In this case, and in others where the contents of the parantheses are identical, there is only one solution: in this case, at:
2x + 1 = 0
ie x = -½

To provide an algebraic summary, we will look at the factorization (ax + b)(cx + d). In this case:
ax + b = 0 or
cx + d = 0
In other words, x = -b/a or x = -d/c. You won't need to remember those exact equations, they are easily deriveable if necessary.

As a final note, if you interpret a quadratic equation as a graph, the roots are indeed the places where the graph cuts the x-axis, because the x-axis is the line y=0. This should help you to see why quadratic equations in general have one, two or sometimes no solutions.

Extension: If you factorize a cubic, quartic, quintic etc. into multiple brackets and are looking for roots, exactly the same method applies: that is, at least one of terms must be equal to zero. This is handy for equations of sixth degree or higher, which have no general solution.

Log in or register to write something here or to contact authors.